2018
DOI: 10.1093/schbul/sby054
|View full text |Cite
|
Sign up to set email alerts
|

Neural Correlates of Auditory Verbal Hallucinations in Schizophrenia and the Therapeutic Response to Theta-Burst Transcranial Magnetic Stimulation

Abstract: Auditory verbal hallucinations (AVHs) are a core symptom of schizophrenia, and resistant to antipsychotic medication in a substantial proportion of patients. This study aimed to investigate the neural correlates of AVHs in schizophrenia patients and its response to a modified continuous theta-burst stimulation (cTBS) by transcranial magnetic stimulation. In a cross-sectional experiment, resting-state functional magnetic resonance images were collected from 31 AVH schizophrenia patients, 26 non-AVH schizophreni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 59 publications
(52 citation statements)
references
References 62 publications
1
51
0
Order By: Relevance
“…This hope was also preliminarily bolstered by our recent works (He et al 2018;Yang et al 2018), in which the music intervention (listening to Mozart music), as a type of the auditory input, improved the functional integration in VAN and SSs in schizophrenia. In addition, considering numerous studies have shown that noninvasive neuromodulation technique, for example, repetitive transcranial magnetic Downloaded from https://academic.oup.com/cercor/advance-article-abstract/doi/10.1093/cercor/bhy232/5112936 by University of Electronic Science and Technology of China user on 18 December 2018 stimulation (rTMS) can produce promising clinical effects in patients with schizophrenia, especially for negative symptoms and auditory hallucinations (Lefaucheur et al 2014;Chen et al 2018), it is worth for future study to explore whether combing sensory-based and rTMS treatment would produce more significant clinical effects than conducting each modality separately.…”
Section: Discussionmentioning
confidence: 99%
“…This hope was also preliminarily bolstered by our recent works (He et al 2018;Yang et al 2018), in which the music intervention (listening to Mozart music), as a type of the auditory input, improved the functional integration in VAN and SSs in schizophrenia. In addition, considering numerous studies have shown that noninvasive neuromodulation technique, for example, repetitive transcranial magnetic Downloaded from https://academic.oup.com/cercor/advance-article-abstract/doi/10.1093/cercor/bhy232/5112936 by University of Electronic Science and Technology of China user on 18 December 2018 stimulation (rTMS) can produce promising clinical effects in patients with schizophrenia, especially for negative symptoms and auditory hallucinations (Lefaucheur et al 2014;Chen et al 2018), it is worth for future study to explore whether combing sensory-based and rTMS treatment would produce more significant clinical effects than conducting each modality separately.…”
Section: Discussionmentioning
confidence: 99%
“…This study aimed to investigate possible imaging correlates of common/specific trans-diagnostic abnormalities. Recently, the neurobiological alterations in SCH and DEP has been investigated using MRI and (EEG) [3][4][5][6][7][8][9] . Volumetric reductions in the gray matter of the prefrontal cortex were consistently reported in SCH 10 .…”
Section: Introductionmentioning
confidence: 99%
“…The cTBS protocol lasted 40 s and consisted of a burst of three pulses delivered at 50 Hz, which was repeated every 200 ms (at 5 Hz) for a total of 600 pulses. This 40-s protocol was repeated three times (1800 pulses in total) with two 15-min breaks (controlled by a stopwatch) (Nettekoven et al, 2014;Ji et al, 2017;Chen et al, 2018). cTBS was performed in a triple way to achieve accumulative aftereffects (Nettekoven et al, 2014).…”
Section: Landerosmentioning
confidence: 99%
“…Functional MRI studies for TMS could be roughly categorized into three classes that focused on immediate (Chen et al, 2013), short-term (Ji et al, 2017), and long-term (Chen et al, 2018) after-effects, respectively. Interleaved TMS and fMRI acquisition could reveal the immediate after-effect seconds after stimulations.…”
Section: Group-level After-effectsmentioning
confidence: 99%